Strategi Pemasaran Digital Produk Aerostreet dalam Meningkatkan Penjualan - Erwin Permana; Andani Alfi Nabil; Erlyn Rosalina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The local fashion industry has experienced significant growth alongside the increasing maturity of Indonesia’s digital ecosystem. Aerostreet is one of the local fashion brands that has benefited from the advancement of digital technology. Initially a footwear brand, Aerostreet has expanded its product range to include clothing, jackets, perfumes, and more. This study aims to analyze Aerostreet’s digital marketing strategies in increasing sales. The research employs a descriptive qualitative approach, with data collected from various official databases and popular websites. In addition to statistical publications, this study also examines scientific publications related to the research problem. The findings indicate that Aerostreet has successfully implemented effective digital marketing strategies to boost sales and strengthen its position in Indonesia’s competitive fashion industry. These strategies include the optimal utilization of social media platforms such as Instagram and TikTok, as well as e-commerce platforms like Shopee, Bukalapak, Tokopedia, and Lazada. On Instagram, Aerostreet builds a positive brand image through engaging visual content, active interactions with followers, and collaborations with other brands. Through TikTok, the brand creates creative and trend-relevant content, encouraging user engagement through hashtag campaigns and challenges. Additionally, Aerostreet maximizes e-commerce by showcasing products in detail and leveraging available promotional features. This combination of strategies enables Aerostreet to reach a broad audience, build brand awareness, and drive product sales. Aerostreet’s success highlights the importance of adapting to digital trends and gaining deep insights into consumer behavior in the digital era.